Decoy oligodeoxynucleotide against STAT transcription factors decreases allergic inflammation in a rat asthma model - Lührmann, Anke; Tschernig, Thomas; von der Leyen, Heiko; Hecker, Markus; Pabst, Reinhard; Wagner, Andreas H. (Experimental lung research, 2010)
Leukocyte infiltration and activation of the CD40-CD40 ligand costimulatory pathway may promote inflammatory processes such as asthma. The aim of this study was to investigate whether a single intratracheal application of a decoy oligodeoxynucleotide (ODN) specific for signal transducer and activator of transcription (STAT) family members 1 and 3 influences leukocyte influx and pulmonary CD40 expression in a rat model of allergic airway inflammation. In comparison with the corticosteroid budesonide, the authors investigated the efficacy of the STAT decoy ODN in ovalbumin-induced allergic asthma in a Brown Norway rat asthma model. Leukocytes of the bronchoalveolar lavage (BAL) and lung tissue were analyzed and expression of CD40 was assessed by Western blotting.
Gesehen am 19.04.2023